Analisis Teknologi Pembuatan Perahu pada Temuan Sisa Perahu Kuno dari Abad VII M di Situs Bongal, Pantai Barat Sumatera Utara - Stanov Purnawibowo; Agni Sesaria Mochtar (Pusat Penelitian Arkeologi Nasional, 2021)
Abstract. The west coast of North Sumatera was a famous sea trade route since the ninth century, according to the research conducted in the Barus Site, the international trading ports in the region. However, the study of the maritime technology in the region is still scarcely done. Boat timbers finding from Bongal Site is the first, as well as the oldest, shipwreck remains found in the west coast of North Sumatera. This paper aims to study the boatbuilding technology, as one of the maritime technologies, of the boat remains found in Bongal Site. Analysis on form and function of the timbers, along with the radiocarbon-dating result of timber and Arenga pinnata rope show that the vessel was built in the Southeast Asian lashed-lugs technique in the seventh century, two centuries older than Barus. Analysis on the artefacts found near the timbers indicates that this type of vessel was used for trade activities on the west coast of North Sumatera.